“I want to, but I lack desire”: The green energy transition caught between expectations and possibilities - Tsoneva, Jana (Identities: Journal for Politics, Gender and Culture, 2025)
In this article, I present results of a nationally representative survey on attitudes toward the Green transition in Bulgaria, which we conducted in 2023 as part of the project “Public Capacity for a Just Green Transition” (KП-06 Н55/13). The survey focuses on four groups of questions concerning climate change, social justice, expectations from the new transition, and the public agenda. Based on these, I draw predominantly pessimistic conclusions about both the Green transition and the transition to liberal democracy preceding it, showing how the experience of the latter inevitably colors the former. I analyze the gap between possibilities and expectations for the new transition with reference to Jacques Lacan’s theorizing about the difference between need/demand and desire.